2010
DOI: 10.4276/030802210x12813483277107
|View full text |Cite
|
Sign up to set email alerts
|

How do Computer Assistive Technologies Enhance Participation in Childhood Occupations for Children with Multiple and Complex Disabilities? A Review of the Current Literature

Abstract: Functional impairments can limit the participation of children with disabilities in childhood occupations, which can be detrimental to their overall development and social and emotional wellbeing. The primary goal of occupational therapy for children with disabilities is to facilitate and enable active participation in meaningful occupations. Computer-based assistive technologies can be used as an enabler, allowing children with severe disabilities access to a variety of activities. The aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 47 publications
1
47
0
2
Order By: Relevance
“…The lack of intervention studies is not unexpected since earlier research identified difficulties in including ICT in education (11,27,77,78) and students' dissatisfaction with access to the computer-based ATDs affects the use of ICT in schools (30). Findings in the descriptive studies showed that ICT is not used in schools to the extent that was desirable from the students' perspective (62,71).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The lack of intervention studies is not unexpected since earlier research identified difficulties in including ICT in education (11,27,77,78) and students' dissatisfaction with access to the computer-based ATDs affects the use of ICT in schools (30). Findings in the descriptive studies showed that ICT is not used in schools to the extent that was desirable from the students' perspective (62,71).…”
Section: Discussionmentioning
confidence: 85%
“…However, for students with disabilities, the literature appears to support the use of ICT as an assistive technology device (ATD), specifically designed to assist and enable an individual's participation, to a varying degree, in all occupational performance areas, but particularly in education, communication and play (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…De fato, o trabalho é uma parte importante da vida para a maioria dos adultos, e as fronteiras entre trabalho e outras esferas da vida são muito permeáveis, por exemplo, estado de humor e de satisfação no trabalho produz impactos no ambiente familiar e social [11][12][13][14].…”
Section: Discussionunclassified
“…For example, assistive technology helped individuals aging with a disability to maintain valued activities and experiences (Kemp 1999), and computer technology aided disabled children in their education and play activities (Chantry and Dunford 2010). In addition, children with physical disabilities mentioned that assistive technology increased their self-confidence and productivity (Carpe et al 2010), and disabled people who used assistive technology in school were more likely to participate in post-secondary education (Bouck, Maeda, and Flanagan 2012).…”
Section: Effects Of Self-help Support Groups and Assistive Technologymentioning
confidence: 99%